The effect of CTLA-4 and CD28 gene variants and circulating protein levels in patients with gastric cancer - Arikan, Soykan; Gümüş, Alper; Küçükhüseyin, Özlem; Coşkun, Cihan; Turan, Saime; Cacina, Canan; Kelten Talu, Canan; Akyüz, Filiz; Farooqi, Ammad Ahmad; Kıran, Bayram; Yaylım, İlhan (Walter de Gruyter GmbH, 2017)
Abstract Objective Gastric cancer is one of the most common malignancies worldwide. The risk factors for gastric cancer include environmental and genetic factors. Inflammation and the immune system are known to contribute to the development of the gastric cancer. We examined the influence of critical polymorphisms of CTLA-4 and CD28 genes and circulating protein levels on the etiology of gastric cancer. Methods Genotyping of SNPs was performed in 55 gastric cancer patients and 105 healthy individuals using the PCR-RFLP method, and circulating levels of sCTLA-4 and sCD28 were measured. Results There were no significant differences in the genotype and allele distributions of the evaluated SNPs [CTLA-4-318 C>T (rs5742909), CTLA-4+49 A>G (rs231775), CD28 C>T (rs3116496)] between gastric cancer patients and controls (p=0.36, p=0.78, and p=0.80, respectively). The circulating levels of sCTLA-4 and sCD28 were significantly different between the gastric cancer group and the control group (p<0.001 and p<0.001, respectively). Conclusion The present results suggest that the CTLA-4 and CD28 gene polymorphisms that were evaluated do not play an important role in Turkish patients with gastric cancer. However, sCTLA4 and sCD28 levels were higher in cancer patients and may be useful as an auxiliary parameter in the diagnosis and monitoring of gastric cancer.
Keywords: 3. Good health